Engineering the Surface of Smart Nanocarriers Using a pH‐/Thermal‐/GSH‐Responsive Polymer Zipper for Precise Tumor Targeting Therapy In Vivo. Issue 36 (18th July 2017) - Zhang, Penghui; Wang, Yan; Lian, Jing; Shen, Qi; Wang, Chen; Ma, Bohan; Zhang, Yuchao; Xu, Tingting; Li, Jianxin; Shao, Yongping; Xu, Feng; Zhu, Jun‐Jie
Abstract : Nanocarrier surface chemistry plays a vital role in mediating cell internalization and enhancing delivery efficiency during in vivo chemotherapy. Inspired by the ability of proteins to alter their conformation to mediate functions, a pH‐/thermal‐/glutathione‐responsive polymer zipper consisting of cell‐penetrating poly(disulfide)s and thermosensitive polymers bearing guanidinium/phosphate (Gu + /pY − ) motifs to spatiotemporally tune the surface composition of nanocarriers for precise tumor targeting and efficient drug delivery is developed. Surface engineering allows the nanocarriers to remain undetected during blood circulation and favors passive accumulation at tumor sites, where the acidic microenvironment and photothermal heating break the pY − /Gu + binding and rupture the zipper, thereby exposing the penetrating shell and causing enhanced cellular uptake via counterion‐/thiol‐/receptor‐mediated endocytosis. The in vivo study demonstrates that by manipulating the surface states on command, the nanocarriers show longer blood circulation time, minimized uptake and drug leakage in normal organs, and enhanced accumulation and efficient drug release at tumor sites, greatly inhibiting tumor growth with only slight damage to normal tissues. If integrated with a photothermal dye approved by the U.S. Food and Drug Administration (FDA), polymer zipper would provide a versatile protocol for engineering nanomedicines with high selectivity and efficiency for clinical cancer treatment. Abstract : pH‐/thermal‐/glutathione‐responsive polymer zippers are screened and explored to tune nanocarrier surface compositions on command for precise tumor targeting in vivo. The nanocarriers remain stealthy during blood circulation, but their surfaces are activated by the acidic microenvironment and photothermal heating at tumor sites for enhanced cellular uptake and efficient drug release, presenting a versatile engineering strategy for nanomedicinal use.